Prevalence of hypertension and its association with stress, Indian diabetes risk score and obesity in rural population of Meerut - Garg, Manish; Bansal, Rahul; Gupta, Monika; Gupta, Chhavi Kiran (Indian Journal of Community Health, 2020)
Background: The prevalence pattern of hypertension in developing countries is different from that in the developed countries. In India, community surveys have documented that between three and six decades, prevalence of hypertension has increased by about 30 times among urban dwellers and by about 10 times among the rural inhabitants. Many studies on hypertension are available from urban areas but there are less studies among the rural population. Aim & objectives: To determine the prevalence & corelates of hypertension among the adults in rural population of Meerut. Settings and Design: community based cross-sectional study conducted in rural Meerut. Materials and Methods: 150 participants were selected by systematic random sampling. Data was collected using a pre designed, structured schedule, including blood pressure and anthropometric measurement of participants. Results: The prevalence of hypertension came out to be 33.3%. In rural population high Indian Diabetes Risk Score (IDRS), higher Body Mass Index (BMI), increased Waist Hip Ratio (WHR), Truncal obesity and disturbed sleep were significantly associated with hypertension, Conclusions: a high prevalence of hypertension was seen in this rural area which requires intervention at primary health care level for its prevention.